The role of media in shaping positive public opinion towards democratic transition and electoral participation in Libya: An analytical perspective based on the theory of prioritizing priorities. (Al-Mukhtar Journal of Economic Sciences, 2022)
The aim of the research is to identify the media role in agenda settingfor audience and shaping public opinion towards democratic transformationand electoral participation. This research relied on the qualitative method andthe second-level meta-analysis of the available published research. Theresearchers analyzed an available sample of research on the role of the mediain democratic transition and electoral participation that the researchers wereable to provide. They reach a number of results, including: The Libyan media played a role towards consolidating the manifestationsof the democratic process in Libya by increasing the democratic awareness ofthe citizens and introducing them to the importance of spreading democracy.- Shedding light on human rights and the importance of preserving humanrights and calling for the detection of any violation of these rights. - Callingfor active and serious participation in the multiple elections that took place inLibya.- Activating the participation of women, whether in decision-making or inplaying a positive political, social, economic and other role.- Introducingpolitical parties and personalities and revealing the electoral programs foreach of them. - Practicing criticism and oversight over governmental,legislative, judicial and other performance. - Standing against calls forseparatism and racism. Informing the citizen of the latest developments in allaspects of Libyan life, politically, economically, socially, and militarily.